Frequency of Negative Appendicectomy after Evaluation by JM Ramirez & J Deus Score - Haider Kamran, Enas Nawaz Khan, Salma Ghaffar, Uzma Shabbir, Muhammad Bilal Akbar, Valeeja Zafar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Acute Appendicitis (AA) is the commonest surgical emergency encountered by surgeon in public & private setup in Pakistan. When it comes to diagnosis, patient seldom presents with the typical bookish picture (symptoms / signs) of the condition. Diagnosis therefore remains an enigma many a times especially for house officers and residents during their emergency duty. Various scores had been developed to aid the diagnosis, Alvarado score although gained popularity and is practiced in our setup. This study was designed to evaluate one such score designed by JM Ramirez & J Deus, for its negative appendicectomy rate calculation with the view to adopt it to our routine practice if it turns out with lesser negative appendicectomy rate compared to other scores in practice. Methods: This descriptive study was designed & carried out at the Surgical “B” Unit of Ayub Teaching Hospital Abbottabad from November 01, 2020 to June 30, 2021. A total of 190 patients with suspected AA were included, assessed by the score and accordingly placed in three groups based upon their initial score. Group-I patients were discharged with the advice to come back to same unit / hospital if pain persists or recurs. Group-II patients were kept in observation for 24 hours and finally re-categorized either as Group-I or Group-III based upon a drop or rise in their score. Group-III patients were operated after preparation. Data collected over a special proforma was finalized at the time of discharge of patient, earlier in case of group I patients or after getting histopathology report in case of Group-III patients that was later analyzed with the help of SPSS-version 26. Results: Out of 190 patients included in study 129 were male while 61 were female patients. 49 patients presented with a score less than –15 (Group–I) & were discharged after evaluation. 53 patients had a score between –15 to 09 (Group–II), were therefore kept under observation till next 24-48 hour. Score of 30 dropped to Group-I range & were similarly discharged like Group-I patients. Score of 23 patients rose up to 10 or above (i.e. Group-III range) & were therefore operated like other 88 patients belonging to Group-III. 91 patients were having acutely inflammed, phlegmonous, gangrenous, perforated appendix or appendix with impacted faecolith / pus in the lumen, their appendicectomy specimen along with the specimen of 20 other difficult to diagnose cases on gross vision were sent for histopathology. H/P report confirmed 100 as positive & 11 as negative for appendicitis. 111 patients totally got operated, out of which 11 turned out negative appendicectomies. Frequency of negative appendicectomies overall was therefore 09.9%. It was 05.56% in male (i.e. 04/72) and 17.94 % (i.e. 07/39) in female patients. Conclusion: Score developed by JM Ramirez and J Deus proved quite helpful in the diagnosis of acute appendicitis & reduction of the frequency of Negative appendicectomies. Being simple, non-invasive & cost-effective, requiring no special equipment or investigations for its application, it ensures an instant, structured & thorough assessment of patient. The score is therefore recommended for its routine adoption / application in our setup in the diagnosis of acute appendicitis to reduce the frequency of negative appendicectomies. Keywords: Acute appendicitis, frequency of negative appendicectomy, scoring system, Ayub Teaching Hospital